Parameters That Effect The Antioxidant Profile And Phenolic Compound From Centella Asiatica Extract - Mohd Bakhtiar, Muhammad Ridhwaan (Universiti Sains Malaysia, 2018)
Centella asiatica is commonly used as a spice and medicinal herb due to its antioxidant activity and total phenolic contents. Water, methanol and ethanol were used to analyze the amount of antioxidant activity and total phenolic contents. Ethanol extraction at 7 hr showed the highest value of DPPH scavenging activity with 65.06 % (IC50=291.00 mg/ml) followed by water with 63.48 % (IC50=408.26 mg/ml) and methanol with 62.39 % (IC50=515.86 mg/ml). The data from the experiment had been compared with the BHT standard curve in order to finalised the best solvent based on DPPH scavenging activity. The increase in DPPH scavenging activity contributes by high amount of TPC. Ethanol gave the highest TPC followed by water and methanol at 228.57 mgGAE/g, 115.63 mgGAE/g and 64.41 mgGAE/g, respectively. This is because ethanol has stronger hydroxyl group compared to methanol and water. The results were compared with the standard curve of gallic acid. As the time increase the phenolic compound from C.asiatica also increase, this is because the phenolic content contributed by capacity of extract due to the time of extraction. The active component that contributed to the phenolic compound is asiaticoside. As The retention time using HPLC was 2.60 min while the standard time was 2.75 min. The result showed that ethanol is the best solvent for extraction of active component with antioxidant activity and phenolic contents of C. asiatica compared to methanol and water.